New methods for the assessment of Parkinson's disease (2005 to 2015): A systematic review. Issue 9 (19th July 2016) - Sánchez‐Ferro, Álvaro; Elshehabi, Morad; Godinho, Catarina; Salkovic, Dina; Hobert, Markus A.; Domingos, Josefa; van Uem, Janet MT.; Ferreira, Joaquim J.; Maetzler, Walter
ABSTRACT: Background: The past decade has witnessed a highly dynamic and growing expansion of novel methods aimed at improving the assessment of Parkinson's disease with technology (NAM‐PD) in laboratory, clinical, and home environments. However, the current state of NAM‐PD regarding their maturity, feasibility, and usefulness in assessing the main PD features has not been systematically evaluated. Methods: A systematic review of articles published in the field from 2005 to 2015 was performed. Of 9, 503 publications identified in PubMed and the Web of Science, 848 full papers were evaluated, and 588 original articles were assessed to evaluate the technological, demographic, clinimetric, and technology transfer readiness parameters of NAM‐PD. Results: Of the studies, 65% included fewer than 30 patients,  < 50% employed a standard methodology to validate diagnostic tests, 8% confirmed their results in a different dataset, and 87% occurred in a clinic or lab. The axial features domain was the most frequently studied, followed by bradykinesia. Rigidity and nonmotor domains were rarely investigated. Only 6% of the systems reached a technology level that justified the hope of being included in clinical assessments in a useful time period. Conclusions: This systematic evaluation provides an overview of the current options for quantitative assessment of PD and what can be expected in the near future. There is a particular need for standardized and collaborative studies to confirm the results of preliminary initiatives, assess domains that are currently underinvestigated, and better validate the existing and upcoming NAM‐PD. © 2016 International Parkinson and Movement Disorder Society